PENGARUH METODE FLIPPED CLASSROOM BERBANTUAN SCHOOLOGY TERHADAP HASIL BELAJAR SISWA DITINJAU DARI KEMANDIRIAN BELAJAR - Najia; Iis Holisin; Himmatul Mursyidah (Universitas Nahdlatul Ulama Sunan Giri Bojonegoro, 2021)
The research aims to describe whether or not there is an effect of the flipped classroom learning method assisted by Schoology on students’ learning outcomes, to investigate the influence between high learning independence and low learning independence on students’ learning outcomes, to investigate the interaction of the use of learning methods and independence learning on students’ learning outcomes, and to analyze student’s activities. The research method used is a quasi-experimental method and uses a 2×2 factorial design with two-way analysis of variance conducted in VIII grade at junior high school Muhammadiyah 5 of Surabaya. The sample in the research was 54 students consisting of VIII-C grade and VIII-E grade. The results showed that the average of students’ learning outcomes in the high and low learning independence categories were 91.00 and 82.00 in the experimental class, respectively, with the percentage of students’ activity classically 66.07% in the sufficient category. While in the control class, the average of students’ learning outcomes in the high and low learning independence categories were 81.053 and 69.625, respectively. Based on the two-way ANOVA test (two-way analysis of variance) shows that there is a significant difference between learning outcomes using the flipped classroom learning method assisted by Schoology and using e-learning which is commonly used in SMP Muhammadiyah 5 Surabaya with the help of Microsoft teams. There is an influence between high learning independence and low learning independence on students’ learning outcomes. However, there is no interaction between learning methods and students’ learning independence on students’ learning outcomes at SMP Muhammadiyah 5 Surabaya. Asbtrak Penelitian ini bertujuan untuk menginvestigasi ada tidaknya pengaruh metode pembelajaran flipped classroom berbantuan schoology terhadap hasil belajar siswa, menginvestigasi pengaruh antara kemandirian belajar tinggi dan kemandirian belajar rendah terhadap hasil belajar siswa, menginvestigasi interaksi penggunaan metode pembelajaran dan kemandirian belajar terhadap hasil belajar siswa dan menganalisis aktivitas siswa. Metode penelitian yang digunakan adalah metode quasi eksperimen menggunakan rancangan factorial 2×2 dengan analisis ANAVA dua jalan yang dilakukan pada kelas VIII SMP Muhammadiyah 5 Surabaya. Sampel pada penelitian ini yaitu 54 siswa terdiri dari siswa kelas VIII-C dan kelas VIII-E. Hasil penelitian menunjukkan rata-rata hasil belajar siswa kategori kemandirian belajar tinggi dan rendah berturut-turut adalah 91,00 dan 82,00 di kelas eksperimen, dengan persentase aktivitas siswa secara klasikal 66,07% dalam kategori cukup. Sedangkan pada kelas kontrol, rata-rata hasil belajar siswa kategori kemandirian belajar tinggi dan rendah adalah 81,053 dan 69,625. Berdasarkan uji ANAVA dua jalan menunjukkan bahwa terdapat perbedaan signifikan antara hasil belajar yang menggunakan metode pembelajaran flipped classroom berbantuan schoology dengan yang menggunakan pembelajaran e-learning yang umum digunakan di SMP Muhammadiyah 5 Surabaya. Terdapat pengaruh antara kemandirian belajar tinggi dan kemandirian belajar rendah terhadap hasil belajar siswa. Namun, tidak terdapat interaksi antara metode pembelajaran dan kemandirian belajar siswa terhadap hasil belajar siswa.